Self-Presentation of Mistresses (Erving Goffman's Dramaturgy Study of Mistresses “Ani-Ani” in Bandung) - Lestari, Anggita; Maulana, Muhammad Dandi; Adi, Achwan Noorlistyo; Putri, Shinta Hartini; Hanafi, Hanafi; Reza, Faisal (Research Collaboration Community (Rescollacom), 2024)
Self-presentation is an effort made by an individual to build a certain impression according to their profession in front of others, including what is done by a mistress (Ani-ani). This study aims to determine the self-presentation of Ani-ani in Bandung according to Erving Goffman's dramaturgy study. This research focuses on the front stage and backstage of the Ani-anis. This research used a qualitative approach with dramaturgy studies. The object of the research is the Ani-anis in Bandung. The selection of informants used a purposive sampling technique where the informants were two Ani-anis in Bandung. The data collection techniques used were in-depth interviews, observations, documentation, and literature studies. The results show that the front stage appearance of the Ani-anis was filled by their behavior when they were with their loyal customers during their quality time. Like Mawar, she used good Indonesian with a gentle, mature, reserved demeanor on the front stage. Meanwhile, Melati used exaggerated Indonesian with a spoiled, seductive, and expressive demeanor. Meanwhile, in the backstage, they displayed their full figure in their daily life, which is completely different from what they showed when they were with their clients. Like Mawar, she often used Sundanese, is lively, religious, and responsible for her family. While Melati was quiet, she used good Indonesian and became a wife who obeyed her husband. This study concludes that every Ani-ani presents themselves in their performances in the front or backstage.